Genetic features of the poxtA linezolid resistance gene in human enterococci from France. (25th April 2021) - Dejoies, Loren; Sassi, Mohamed; Schutz, Sacha; Moreaux, Julie; Zouari, Asma; Potrel, Sophie; Collet, Anaïs; Lecourt, Maxime; Auger, Gabriel; Cattoir, Vincent
Abstract: Objectives: To describe the prevalence of poxtA among clinical linezolid-resistant enterococci (LRE) collected in France from 2016 to 2020 and to extensively characterize its genetic supports and environments. Methods: All LRE clinical isolates received at the National Reference Centre for Enterococci from French hospitals between 2016 and 2020 were included. LRE isolates were screened for linezolid resistance genes ( cfr -like, optrA and poxtA ) by real-time PCR and phenotypically characterized. A collection of 11 representative poxtA -positive isolates (10 Enterococcus faecium and 1 Enterococcus faecalis ) underwent WGS by hybrid assembly combining short-read (Illumina MiSeq) and long-read (MinION) approaches. Transferability of poxtA was attempted by filter-mating experiments. Results: Out of 466 LRE received at the National Reference Centre for Enterococci over the period, 47 (10.1%) were poxtA- positive, including 42 E. faecium . The 11 isolates characterized by WGS were confirmed to be epidemiologically unrelated by core genome analysis and eight different STs were assigned to E. faecium isolates. The poxtA gene was found to be plasmid carried and flanked by IS 1216E transposase genes in all isolates and frequently linked with fexB, tet (M) and tet (L). A total of seven distinct poxtA -harbouring plasmids were obtained after hybrid assembly and plasmid transfer of poxtA was successful in three cases. For the two poxtA / optrA -positive isolates, those genes were carried by different plasmids. Conclusions: The poxtA gene has been circulating among clinical enterococci in France since at least 2016, mostly in E. faecium and independently from optrA . The poxtA -carrying plasmids often co-carried resistance genes to phenicols and tetracyclines, and could have been co-selected through their veterinary use.